Inter-annual and seasonal variations in the Outer and Inner Sea spawning zones of southern hake, Merluccius australis, inferred from early life stages distributions in Chilean Patagonia. (February 2019) - Flores, Eduardo A.; Castro, Leonardo R.; Narváez, Diego A.; Lillo, Sergio; Balbontín, Fernando; Osorio-Zúñiga, Francisca
Highlights: The Outer Sea is the main spawning zone for southern hake in winter. The Inner Sea of Chiloé is the main spawning zone in the Inner Sea during spring. Oceanographic conditions were different between the Outer and Inner Sea. The Outer Sea oceanographic condition had important inter-annual variation. Potential retention zones were identified in the Outer and Inner Sea. Abstract: Merluccius australis, known as southern hake, is a demersal fish that inhabits waters off the southern tip of South America. The main spawning area has historically been located in the Outer Sea off northern Chilean Patagonia, where these fish aggregate to reproduce during austral winter. An alternative spawning ground has been reported to occur within the Inner Sea of Chiloé, where eggs of a few days old have been found. Neither the relative importance of this spawning zone nor the main environmental features that make it suitable for spawning have been assessed. We analyzed ichthyoplankton samples and hydrographic data from oceanographic cruises (2003–2015) carried out in austral winter and spring to characterize both spawning zones. Field data showed, on average, 30 and four times more southern hake eggs in the Outer Sea than in the Inner Sea for winter and spring, respectively. Accordingly, the species mainly spawns during winter in the Outer Sea but during spring in the Inner Sea. Potential retention zones were identified, and the spawning seasons for both areas were associated with local oceanographic processes that enhanced retention in nursery areas. The development of different main reproductive seasons in different zones is apparently linked to the inter-annual variability of environmental conditions in the main offshore spawning zone. In this case, secondary spawning in the Inner Sea could be part of a reproductive strategy to ensure offspring survival given unfavorable conditions in the Outer Sea.